Effect of exhaust gas stream recirculation on emission from a palm oil mill boiler - Chong, Woon Chan (2012)
This study aimed to investigate the gases and particulate emissions from a palm oil mill boiler, the effect of exhaust gas stream recirculation on multi-cyclones performance, and particulates characteristics on the size distribution and elemental composition. A palm oil mill plant situated in Kulai, Johor was chosen as the study site. The mill was equipped with a multi-cyclones connected with a recirculation duct from the outlet to the inlet of the unit. Different recirculation airflow rates (0%, 11% and 17% of the total exhaust gas flow rate) were available by the means of external induced draft (ID) fan to extract part of the exhaust gas stream from the multi-cyclones outlet back into its inlet. The flue gas volumetric flow rate and particulate concentration were measured at the boiler outlet (cyclone inlet), stack gas (emitting the cyclone) and recirculation duct using US EPA methods. The average concentration of O2 measured was 16.9% while the average concentration (corrected to 7% O2) of CO2, CO, NO and SO2 measured was 2.93%, 5153 mg/Nm3, 84.2 mg/Nm3 and 339 mg/Nm3, respectively. Besides, the particulate emission factor based on 27,000 kg/hr fresh fruit bunch (FFB) processed, 6,000 kg/hr fibre and shell (F and S) burned, and 8,000 kg/hr boiler capacity (BC) was 5.45 ± 2.18 g/kg, 24.5 ± 9.82 g/kg, and 18.4 ± 7.36 g/kg, respectively. From the result, with the increase of inlet particulate loading, the performance of the multi-cyclones was able to achieve 74% collection efficiency at 11% recirculation rate, with an increment of 6% compared to without recirculation (68%). The performance, however, dropped to 67% at 17% recirculation rate because the recirculated particulates were broken up into smaller size fraction at higher recirculation rate when passing through external ID fan. At 11% recirculation rate, most of the elemental concentrations (Fe, Mn, Cr, V, As and Co) were reduced along with reduction of fine particulates emitted